INNOVATIVENESS OF DIFFERENT AGRICULTURAL TYPES OF FARMSIN FARMERS’ OPINION FROM REGIONS OF MAZOWSZE AND PODLASIE - Adam Harasim; Andrzej Madej; Andrzej Górnik (Annals of the Polish Association of Agricultural and Agribusiness Economists)
The objective of the study was to survey the opinion of the operators of different types agricultural of farms (cattle,pig, mixed, and crop farms) situated in the regions of Mazowsze and Podlasie regarding the issue of innovations inagriculture. The aim of the study was to learn about the sources of information on innovations in agriculture and aboutthe demand for agricultural counseling. Purposeful selection of the sample was used and farmers’ opinions were surveyedby the query method. Pro-innovative attitudes were shown by the majority of the owners of cattle and crop farms. Theowners of all types of farms usually drew upon the following sources of information: ODR (Agricultural AdvisoryCentres) extension officers, technical journals, training courses, internet and television. Livestock farms (cattle andpig farms) showed a greater demand for extension services that did mixed production farms. Of the extension servicespresent, consulting by ODR’s workers and by agricultural agencies were in the greatest demand.